Penerapan Community Crime Prevention Pada Operasi Satgas Intelijen Perbantuan Madago Raya BNPT Di Poso - Mediansyah, Rezky; Supriadi, Supriadi; Djatmiko, Mochamad (University of Muhammadiyah Malang, 2024)
Terrorism is one problem faced by various countries in the world, including Indonesia. The losses caused by terrorism are so great that this issue needs special attention. From many various sub-problems in terrorism in Indonesia, the movement of Mujahidin Indonesia Timur (MIT) in the Poso area is one of the problems that is quite difficult to overcome. Because the challenges are so tough, and the community in Poso prefer to support the MIT movement because of their threats. Therefore, community as the side who is considered the most able to secure themselves to be powerless. Therefore, Badan Nasional Penanggulangan Terorisme formed a Madago Raya Assistance Intelligence Task Force which has the task for recruiting the community so that they can actively participate in assisting law enforcement against MIT. This study will evaluate the process of fundraising that is carried out through the framework of the concept of community crime prevention.